2019
DOI: 10.1002/1878-0261.12445
|View full text |Cite
|
Sign up to set email alerts
|

CA10 and CA11 negatively regulate neuronal activity‐dependent growth of gliomas

Abstract: Recent studies have revealed that neurons can promote glioma growth through activity‐dependent secretion of neurotrophins, especially neuroligin‐3. It has therefore been suggested that blocking neuron‐derived neurotrophins may serve as a therapeutic intervention for gliomas. Carbonic anhydrase‐related proteins 11 and 10 ( CA 11 and CA 10) are secreted synaptic proteins which function as neurexin ligands, and the gene‐encoding CA 11 is part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The protein encoded by CA10 is involved in brain development and the central nervous system [41]. Moreover, a bioinformatics study revealed 15 genes, including CA10, to be hub genes and able to predict the occurrence of AD [42].…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by CA10 is involved in brain development and the central nervous system [41]. Moreover, a bioinformatics study revealed 15 genes, including CA10, to be hub genes and able to predict the occurrence of AD [42].…”
Section: Discussionmentioning
confidence: 99%
“…The SNP was found in an intronic region of the carbonic anhydrase gene ( CA10 ) (position 289,041 within the 309,442 bp of the gene) (Figure 1b). The protein coded by CA10 is catalytically inactive and recent findings point to an evolutionary conserved function as a ligand of neurexin in the presynapses of the central nervous system (Sterky et al, 2017; Tao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…CA10 , encoding a non-catalytic related protein acting as a ligand for neurexins in neurons [ 30 ], was also found in our study as a transcript important for age prediction. It is also downregulated in gliomas, with lower expression among glioma patients associated with high grade subtype and shorter survival [ 31 ]. Considering its important role in synaptic Ca 2+ signaling via neurexin, as well as its association with glioma, an aging-related disease, our results showing the importance of CA10 transcript in age prediction may be important.…”
Section: Discussionmentioning
confidence: 99%